Modelamiento del proceso de formación de la viruta utilizando el método de elementos finitos - Chunga Sánchez, Luis Antonio (2019)
The machining process is one of the most used manufacturing methods in the industry, to carry out the planning of machining processes is essential to take into account the most relevant aspects of the piece and the tool such as: the life of the tool, the accuracy and integrity of the surface of the components to be machined, the direction of exit, size and geometry of the chips. Loads on the tool, workpiece and accessories. The main reasons that motivate the development of models for machining are: Prediction of important processing parameters such as cutting force, rate of heat generation, energy consumption, and vibrations; development of effective tools for planning the process to improve the design, reliability and operation of machine tools. Specifically, finite element method modeling techniques and non-mesh methods have shown promising results, but more research work is required to improve the ability of these models to represent the actual physical process of chip formation. Therefore, the investigation of the modeling of the metal machining process has a great validity, based on the need for a greater understanding of the process and the phenomena that involve it. For this work the phenomenon of formation of metal shavings is studied as a problem that presents very high plastic deformations at very high temperatures. Using the principles of material resistance and the equations of the mechanics of the continuous media. For the development of this work, a preliminary work is done by the finite element method (MEF) and commercial software.